Slow light in metamaterial heterostructures - K. L. Tsakmakidis; Hess, O. (Proceedings of SPIE - The International Society for Optical Engineering, 2008)
A competent method for slowing and completely stopping light, based on wave propagation along an adiabatically tapered negative-refractive-index metamaterial heterostructure, is presented. It is analytically shown that, in principle, this method simultaneously allows for broad bandwidth operation (since it does not rely on group index resonances), large delay-bandwidth products (since a wave packet can be completely stopped and buffered indefinitely) and high, almost 100%, in/out-coupling efficiencies. Moreover, by nature, the presented scheme invokes solid-state materials and, as such, is not subject to low-temperature or atomic coherence limitations. A wave analysis, which demonstrates the halting of a monochromatic field component travelling along the heterostructure, is followed by a corresponding ray analysis that illustrates the trapping of the associated light-ray and the formation of a double light-ray cone ('optical clepsydra'). This method for trapping photons conceivably opens the way to a multitude of hybrid, optoelectronic devices to be used in 'quantum information' processing, communication networks and signal processors, and may herald a new realm of combined metamaterials and slow light research.
cited By 1